Verticalização imobiliária e controle do uso e da apropriação do espaço urbano em Belém: discursos e conflitos em torno da outorga onerosa do direito de construir - VIEIRA, Bruno Soeiro (Universidade Federal do Pará, 2017)
This thesis aimed to comprehend the process of real estate verticalization in the urban area of Belém (PA) and its correlation with the Onerous Building Right (OODC), a legal instrument which can assist the municipalities to order the use and occupation of the cities space, as well as to promote an equitable distribution of it benefits and burdens arising from the urbanization process. As methodology, it is provided a discourse analysis, by interviewing the social agents responsible for the urban space distribution and its decision making process, with the aid of the available data, mostly collected from the local press. With the discourse analysis it is possible to capture the different understandings of the local development planning process, specially the verticalization process and OODC enforcement by the municipality. As a result, it was possible to identify the discourse convergences and divergences, the conflicts among different social agents, their ideology and the decision making power game shift inherent to the space urban configuration. Among the conclusions reached with this doctoral thesis, the analysis of the discourses showed that in Belém, a kind of non-institutionalized alliance signed between real estate developers and the municipal executive branch in favor of a conception of urban development planning that makes impossible the guarantee of the right to sustainable cities foreseen in the City Statute (BRASIL, 2001), that is, such discursive agents emit arguments in favor of a paradigm that is clearly antidemocratic, segregating, unjust and unsustainable, resulting, in particular, in the ineffectiveness of the Onerous Building Right in Belém. In addition, it was also clear that the lack of application of the urban-environmental instrument in question is also justified by the inexpressive power of organization of civil society which, as a consequence, results in a fragile and timid power of social mobilization and political pressure in favor of a model of sustainable socio-spatial development in municipality of Belém.